Long-term outcomes of patients with primary brain tumors after acute rehabilitation: a retrospective analyses of factors - Tay, Matthew Rong Jie (2023)
Although primary brain tumors are relatively rare, they cause significant morbidity and mortality due to the high rates of neurological impairment. The purpose of this study was to examine the physical and functional outcomes of patients with primary brain tumors who had undergone inpatient rehabilitation. This was a retrospective study which recruited 163 patients who had been admitted for inpatient rehabilitation. Rehabilitation outcomes, including the Functional Independence Measure (FIM) and Glasgow Outcome Scale (GOS), were recorded up to 1 year post-discharge. The majority of patients (79.1%) had low-grade (WHO Class I-II) tumors, 35 (21.5%) were diagnosed with GBM and 52 (31.9%) had recurrent brain tumors. Rehabilitation outcomes were sustained, with 125 (76.7%) and 113 (69.3%) patients having a GOS of ≥4 at 6 months and 1 year after discharge, respectively. A GOS of ≥4 at 1 year was negatively associated with high-grade tumors (p < 0.001) and radiotherapy (p = 0.028), and positively associated with a higher discharge FIM motor score (p < 0.001) and the presence of a caregiver after discharge (p = 0.034). Our study demonstrates significant positive functional benefits from 4 weeks of inpatient neuro-oncological rehabilitation for patients with primary brain tumors, as well as the importance of supportive care from caregivers.